Control and monitoring of the Znosko Glacier in Antarctica - Fabian Brondi Rueda; Gabriele Garnero; Giovanni Righetti; Stefano Serafini (2020)
The study and analysis of climate change is a global challenge against which environmental, but also economic and social changes, will be measured. This memorandum illustrates the recent activities carried out by the IGN Peru in collaboration with European institutions.